‘He Who Rides the Tiger Cannot Dismount’ Implementation of E-learning Within Company Strategies - Williams, Sadie; Burgoyne, John (Proceedings of the International Conference on Networked Learning, 2002)
This paper reports research on the collective behaviour of corporate organisations in relation to the adoption and use of e-learning, including the extent to which there are strategies guiding this, integrating it with other corporate processes. Our overall conclusion is that while rational justifications are usually used for the startup and initial investment in e-learning provision, the sequence of activities that follow from this tend not to fit with the original plan or vision, but despite this they are not abandoned but carry on based on different and emergent logics, or simply because they have become an established ongoing activity of these organisations. Our evidence supports the view that corporate e-learning shapes and evolves in ways that are different from education based e-learning. Although the scale, investment and aspiration of corporate e-learning is often larger than that in an educational setting the planning and designing is less careful, and the steering of this through formative and summative evaluation is rarely undertaken. In some corporate settings use of e-learning is highly integrative of initiatives to provide learning assistance, job focused decision support systems and the implementation of corporate knowledge management strategies. In others, it is none of these things. We suggest that e-learning strategies based on economy, substitution and extended reach should be replaced by strategies that link the e-learning provision to the knowledge management implications of the corporate strategies and business models being pursued by organisations.